Three-Dimensional Beam Propagation Modeling of Nanostructured Whispering-Gallery Microcavities - Mohammad Amin Cheraghi Shirazi; Serge Vincent; Tao Lu (IEEE Photonics Journal, 2016)
Using a scalar 3-D beam propagation technique in a cylindrical coordinate system, we demonstrate that a nanohole bored in a whispering-gallery microcavity sensor with an inserted 25-nm-radius polystyrene particle can dually enhance the detection signal (by a factor of $\sim$ 6) and maintain a quality factor of $7.6 × {10^{8}}$ (after degradation by a factor as little as 3) at a wavelength of 633 nm. Detailed numerical characterization of the resonant light circulating in this nanostructured cavity is provided, including aspects of stability and convergence.